Positionsbestimmung in der Paar- und Familienpsychologie - Guy Bodenmann (Journal of Family Research, 2006)
This article tries to resume some of the theoretical and empirical issues that attract currently high attention within the field of marital and family psychology. Although no exhausting overview can be given, some relevant topics are presented and discussed with regard to basic research in family psychology and their application in prevention and psychotherapy. Themes that merit more consideration in the future are also addressed.